Sistem Informasi Catholic Center Medan Berbasis Web - Panjaitan, Mei Yanti; Damanik, Romanus (MEANS (Media Informasi Analisa dan Sistem), 2018)
At present, many people use technology as a material to simplify work, the technology used is technology based online and offline. Nowadays technology is also used as a medium for the wider community to get information and communicate with each other wherever and whenever. Catholic Center "Christosophia" Medan Archdiocese, is engaged in an integrated service center that aims to improve services for all Catholics and other religious institutions. Catholic Center Archdiocese of Medan also provides various places such as: meeting room, lodging, hall and prayer room data. The resulting web display can provide convenience in terms of leasing in a web-based terrain catholic center, the advantage of this system is that there is a member and non-member system that is to improve the quality of building leases made by customers, and if the customer is a member then the customer can get discounted place price with the stipulated conditions. And with the system of members and non-members, it will make customers satisfied with the service and excellence available at the Catholic Center, and can help leaders maintain their customers and find new customers.